Epidemiologia da podridão-de-fusário em frutos de meloeiro - OLIVEIRA, Michelle Jardelina de (2007)
The Fusarium rot, caused by the fungus Fusarium pallidoroseum, is an important postharvest disease of melon (Cucumis melo) fruits in the Brazil. This work aimed to analyze the influence of the inoculation method (pulverization, drop deposition, pulverization with wound, drop deposition with wound, and sub-epidermal injection), wound age (0, 12 and 24 hours), humidity (with and without moist chamber), temperature (10, 15, 20, 25, 30 e 35°C) and inoculum concentration (101, 102, 103, 104, 105, 106 conidia/mL-1) of three F. pallidoroseum isolates (CF-589, CF-685 and CF-687) on the severity of the Fusarium rot in melon fruits type Cantaloupe (cv. Torreon) and Honeydew (cv. Orange Flesh). The three F. pallidoroseum isolates had provoked symptoms of Fusarium rot in the evaluated situations, but they had not differed significantly (P=0,05) between itself how much to the severity levels of disease, as well as had not been evidenced significant interactions with melon’s cultivars. On the other hand, in all the experiments had been evidenced significant differences in the disease levels between two melon’s cultivar, with cv. Torreon presenting levels of disease’s severity significantly higher to the evidenced on Orange Flesh cultivar. It did not haveseverity significantly higher to the evidenced on Orange Flesh cultivar. It did not have development of injuries in the fruits when the inoculations had been carried without wound. The inoculation for atomization of the conidia’s suspension propitiated the biggest injuries in the submitted fruits at wounds. The inoculation for sub-epidermal injection caused lesser injuries than methods of atomization or drop with wound. It had the reduction of the severity of the disease in the fruits with the increase of the age of the wound. The injuries had been significantly lesser in the wounded fruits 24 hours before the inoculation than in those wounded fruits with 12 hours before or immediately before the inoculation. The free water presence in the surface of the fruits was unnecessary for the beginning of the infection’s process for F. pallidoroseum isolates, even so the injuries has been bigger in the fruits submitted to the humid chamber. The temperature significantly influenced the severity of the Fusarium rot, being that the optimum temperatures estimated for the disease’s development were 23,9 °C e 23,0 °C, respectively for Orange Flesh e Torreon cultivar. The severity of the disease increased with the increment in the inoculum concentration of F. pallidoroseum. The biggest injuries had been observed in the concentration of 1x106 conidia/mL-1 in the twocultivars, but same in lesser inoculum concentration (1x101 conídios/mL-1), they registered considerable levels of disease. The inoculum concentration necessary to generate 50% of the maximum size of the injury Orange Flesh cultivar was four times higher than that demanded for Torreon cultivar.